Design and application of a disposable pack for warm and cold compress treatment (一种新型一次性冷热敷袋的设计与应用) - SHAO Jianmin (邵建敏); GAO Xiaoyan (高小艳); MA Xiaodi (马小娣); XU Yuanle (许远乐) (中西医结合护理)
This paper introduced the design and application of a disposable pack for warm and cold compress treatment. This easy-to-use and disposable pack has been designed to ensure the comfort of the patient when receiving warm and cold compress treatment. (冷敷和热敷临床常见护理操作, 冷热敷袋是必不可少的辅助工具。本研究设计一种新型一次性冷热敷袋, 既兼顾使用便利性, 同时还能保障患者舒适度。)